Molecular characterisation of hepatitis B virus in HIV-1 subtype C infected patients in Botswana - Anderson, Motswedi (BMC Infect Dis, 2015)
BACKGROUND: Hepatitis B virus (HBV) is a major global health problem especially in sub-Saharan Africa and in East Asia. Ten hepatitis B virus genotypes have been described that differ by geographic distribution, disease progression, and response to treatment. Escape mutations within the surface open reading frame (ORF) affect HBV antigenicity leading to failures in diagnosis, vaccine and hepatitis B immunoglobulin therapy. However, the molecular characteristics of HBV in Botswana, a highly endemic country, are unknown. We describe the molecular characteristics of HBV and prevalence of escape mutants among HIV/HBV coinfected individuals Botswana. METHODS: DNA was extracted from archived plasma samples from 81 HIV/HBV co-infected participants from various clinical studies at the Botswana Harvard AIDS Institute Partnership. A 415 base pair (bp) fragment of the polymerase gene was amplified by semi-nested PCR. In a subset of samples, a 2100 bp fragment was amplified. The PCR product was genotyped using Big Dye sequencing chemistry and the sequences were analysed for genotypes and mutations. RESULTS: Of the 81 samples included, 70 (86 %) samples were successfully genotyped. Genotype A was found in 56 (80 %) participants, D in 13 (18.6 %), and 1 (1.4 %) was genotype E. Escape mutations previously linked with failure of diagnosis or escaping active vaccination and passive immunoglobulin therapy were detected in 12 (17.1 %) participants at positions 100, 119, 122, 123, 124, 126, 129, 130, 133, 134 and 140 of the S ORF. Genotypes and escape mutations were not significantly associated with aspartate aminotransferase (AST), alanine aminotransferase (ALT) and AST platelet ratio index (APRI). CONCLUSION: Genotypes A, D and E were found in this cohort of HIV coinfected patients in Botswana, consistent with the findings from the sub-Saharan Africa region. Some escape mutations which have previously been associated with diagnosis failure, escaping vaccine and immunoglobulin therapy were also observed and are important in guiding future policies related to vaccine implementation, therapeutic guidelines, and diagnostic guidelines. They are also important for identifying patients who are at an increased risk of disease progression and to choose optimal therapy. Future research should focus on determining the clinical significance of the different HBV genotypes and mutations found in this population.